2021
DOI: 10.3390/ani11061522
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Milk-Derived Small Extracellular Vesicles Promote Intestinal Immunoglobulin Production through pIgR

Abstract: Secretory immunoglobulin A (SIgA) plays an important role in gut acquired immunity and mucosal homeostasis. Breast milk is the irreplaceable nutritional source for mammals after birth. Current studies have shown the potential functional role of milk-derived small extracellular vesicles (sEVs) and their RNAs cargo in intestinal health and immune regulation. However, there is a lack of studies to demonstrate how milk-derived sEVs affect intestinal immunity in recipient. In this study, through in vivo experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Mounting evidence reports that porcine colostral exosomes may contribute to the healthy growth and/or development of piglets [ 5 , 6 , 10 ]. In the present study, we evaluated the effect of porcine milk-derived exosomes, focusing on those from colostrum, on T cells in the peripheral blood of suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence reports that porcine colostral exosomes may contribute to the healthy growth and/or development of piglets [ 5 , 6 , 10 ]. In the present study, we evaluated the effect of porcine milk-derived exosomes, focusing on those from colostrum, on T cells in the peripheral blood of suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 5 ] suggested that exosomes in the porcine milk stimulated the proliferation of small intestinal epithelial cells in vitro. In addition, Zeng et al [ 10 ] demonstrated that exosomes in porcine milk (collected 3–5 days post-parturition) promoted intestinal immunoglobulin production by stimulating the expression of polymeric immunoglobulin receptors both in vitro and in vivo. These reports seemed to imply that porcine colostral exosomes contributed to the growth and/or development of suckling piglets.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific mechanism of how LFM affects PIGR expression levels remains incompletely understood. Interestingly, a recent study demonstrated that porcine milk small extracellular vesicles (PM-sEVs) circ-XPO4 plays an important role in IPECJ2 cell or recipients through the absorption of miR-221-5p and activation of the PIGR , and eventually promote intestinal sIgA production in piglet [ 61 ]. In addition, previous research suggested that most of the beneficial activities from breast milk may be provided by its microbiota associated metabolites, and one clinical trial of Lactobacillus paracasei CBA L74-fermented formula indicated that Lactobacillus fermented milk has a nutritional value similar to breast milk in term of promoting intestinal sIgA level [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Moon et al, 2015). The study showed that miR-221-5p could target polymeric immunoglobulin receptor (pIgR), which is closely related to the sustained supply of secretory IgA, reducing the intestinal secretory IgA level (Bruno et al, 2011;Zeng et al, 2021). Activation-induced cytidine deaminase (AID), a key enzyme of intestinal immune antibody, was targeted by miR-155.…”
Section: Mirnas Regulate the Homeostasis Between Gut Microbiota And The Hostmentioning
confidence: 99%